Influence of In2O3 Addition On The Magnetic And Electrical Properties of Iron Deficient Ni-Zn Ferrite - Akhter, Shireen; Choudhury, Md Amanullah; Rahman, J (Journal of Bangladesh Academy of Sciences, 2012)
The influence of low melting In2O3 addition on the magnetic and electrical properties of irondeficient ferrites of composition. Ni0.65Zn0.35Fe1.96O4 + xIn2O3(x = 0, 0.005, 0.01, 0.015, 0.02, 0.025, 0.03 and 0.035) was investigated. Single phase spinel structure of all sintered samples were confirmed by X-ray diffraction. The lattice parameter of the samples increased with the increment of In2O3. The effect of In2O3 (melting point 680°C) can be explained by the formation of liquid phase on the grain surface due to reaction of In2O3 with the spinel phase at 1250°C sintering temperature. Saturation magnetization decreased almost linearly and Curie temperature linearly with the increasing addition of In2O3. The decrease in magnetization was possibly due to diamagnetic In3+ ions occupy B-sublattice ( octahedral sites) and replace Fe3+ ions keeping the magnetization of A-sublattice (tetrahedral sites) unchanged. When indium ions occupy B-sites and replace Fe3+ ions, the magnetization of B-sublattice (MB) decreases keeping the magnetization of A-sublattice (MA) constant which in turn weakens A-B exchange interaction (M = MB-MA). The dc resistivity of the samples increased almost linearly with the addition of In2O3. With the increasing addition of In2O3, In3+ ions occupy B-sites which reduces Fe2+ to Fe3+ electron hoping conduction in octahedral sites and contributes to increase in resistivity. DOI: http://dx.doi.org/10.3329/jbas.v36i2.12957 Journal of Bangladesh Academy of Sciences, Vol. 36, No. 2, 153-158, 2012